Cannabis sativa L. Miniature Inverted-Repeat Transposable- Element Landscapes in Wild-Type (JL) and Domesticated Genome (CBDRx) - Quiroga, Mariana Paola; Crociara, Clara Sonia; Schenfeld, Esteban Martín; Fernandez, Franco Daniel; Crescente, Juan Manuel; Vanzetti, Leonardo Sebastian; Helguera, Marcelo (MDPI, 2025)
Cannabis sativa L. is a globally cultivated plant with significant industrial, nutritional, and medicinal value. Its genome, comprising nine autosomes and sex chromosomes (X and Y), has been extensively studied, particularly in the context of precise breeding for specific enduses. Recent advances have facilitated genome-wide analyses through platforms like the NCBI Comparative Genome Viewer (CGV) and CannabisGDB, among others, enabling comparative studies across multiple Cannabis genotypes. Despite the abundance of genomic data, a particular group of transposable elements, known as miniature inverted-repeat transposable elements (MITEs), remains underexplored in Cannabis. These elements are non-autonomous class II DNA transposons characterized by high copy numbers and insertion preference in non-coding regions, potentially affecting gene expression. In the present study, we report the sequence annotation of MITEs in wild-type and domesticated Cannabis genomes obtained using the MITE Tracker software. We also develop a simple and innovative protocol to identify genome-specific MITE families, offering valuable tools for future research on marker development focused on important genetic variation for breeding in Cannabis sativa.